Influence of Gd3+ on molecular organization and electrochemical properties of Si-based organic/inorganic sol-gel layers. (1st May 2020) - Fedel, Michele; Callone, Emanuela; Ziarelli, Fabio; Deflorian, Flavio; Dirè, Sandra
Abstract: Lanthanoid cations are commonly employed as active corrosion inhibiting agents inside sol-gel coatings derived from organosilanes. However, the effect of lanthanoids on the structure of sol-gel coatings derived from organoalkoxysilanes is still not completely clear and object of debate. Even if it has been reported that lanthanoid ions have a beneficial effect in terms of corrosion protection properties, it has not been completely understood if it is related to the active inhibition of the local electrochemical activity or to a modification of the sol-gel coating structure. In addition, it is still not clear how the lanthanoid ions are distributed in. In order to get some insights into the effect of lanthanoids on the structural and electrochemical properties of sol-gel layers, the present work employs gadolinium ions. Gd was selected also for its magnetic and electronic properties, which strongly affects the signals intensity of many spectroscopy techniques. Accordingly, Gd ions act as a marker to evaluate the localization of lanthanoids in the hybrid network. The structural effect on the sol-gel films promoted by the addition of gadolinium ions has been assessed by means of solid state nuclear magnetic resonance (NMR), Fourier transform infrared (FT-IR) spectroscopy and electron spin resonance (ESR) spectroscopy. The structural features of the Gd-doped coatings have been correlated with their electrochemical response obtained by means of polarization curves and electrochemical impedance spectroscopy (EIS). Graphical abstract: Image 1